PENGARUH ADOPSI E-COMMERCE DAN SOCIAL MEDIA MARKETING TERHADAP KINERJA UMKM DI MEDIASI OLEH ENTREPRENEUR ORIENTATION - Bunadi, Andreanto; Nurlinda, RA (ANALISIS, 2023)
The study's goals are to, ascertain the direct impact of e-commerce adoption and SMM on entrepreneur orientation; assess the direct impact of entrepreneur orientation and SMM on MSME performance; and examine the indirect impact of e-commerce adoption and SMM on MSME performance by way of entrepreneur orientation. A questionnaire survey was used to obtain the data. Google form-based survey distribution through social media. The focus of this analysis is on small and medium-sized businesses (SMBs) in the Bangka Belitung region that have used e-commerce and social media marketing strategies. Up to 170 people filled out the survey. This research used a non-probabilistic, purposive sampling strategy. A favorable correlation between entrepreneurism and the use of e-commerce and social media marketing was found in the study's analysis. The success of micro, small, and medium-sized enterprises (MSMEs) may be improved by the use of e-commerce, social media marketing, and an entrepreneurial mindset. Both the use of social media for marketing purposes and the use of e-commerce may improve the performance of micro, small, and medium-sized enterprises (MSMEs) by encouraging the development of an entrepreneurial mindset. The study's findings will hopefully serve as a guide for micro, small, and medium-sized enterprise (MSME) players as they consider whether and how to include e-commerce and social media marketing into their operations.